Consistent Condom Use and Associated Factors among HIV-Positive Clients on Antiretroviral Therapy in North West Ethiopian Health Center, 2016 GC - Mohammed Seid Ali; Eleni Tesfaye Tegegne; Mekibib Kassa Tesemma; Kaleab Tesfaye Tegegne (AIDS Research and Treatment)
Background. The burden of Human Immune Deficiency Virus or Acquired Immune Deficiency Syndrome is high in sub-Saharan countries including Ethiopia which have over two-thirds of the global HIV burden. Many would argue that consistent condom use is not most effective method for HIV prevention. Condoms offer protection against unwanted pregnancy and some sexually transmitted infections including Human Immune Deficiency Virus, when used correctly and consistently. Inconsistent use of condom by People Living with Human Immune Deficiency Virus or Acquired Immune Deficiency Syndrome on Antiretroviral Therapy will lead to further worsening the Human Immune Deficiency Virus infection epidemic and reinfection with new drug resistant viral strains. Objective. To assess magnitude of consistent condom use and associated factors among HIV-positive clients on Antiretroviral Therapy in North West Ethiopian health center, 2016 GC. Method. An institutional based cross-sectional study was conducted, from April 15 to June 10, 2016. A total of 358 patients on ART in Koladiba Health Center had participated in this research. Koladiba Health Center is the first health center in Ethiopia that is found in Debbie district, which is located in north Gondar Zone. Study participants were selected by simple random sampling technique. Data were collected by using pretested structured questionnaires and analyzed using SPSS version 22. Descriptive statistics was computed and binary and multiple logistic regressions were also conducted to examine the effect of selected independent variables on consistent condom use. Result. A total of 358 ART clients participated in the study with response rate of 90%. Among study participants, 138 (38.5%) were in the age category of 35-44 years. About 216 (60.3%) of the participants were female and 325 (90.8%) were Orthodox followers. Consistent condom use was reported by 130 (55.8%) sexually active study subjects. Respondents in rural residence (AOR=0.326, 95% CI: 0.109, 0.973) and sexual partner initiated condom use (AOR=0.031, 95% CI: 0.005, 0.186) were found to be the independent predictors of consistent condom use. Conclusion and Recommendations. Consistent condom utilization among HIV clients on ART was low (55.8%). Place of residence and condom use initiation during sexual contact were significantly associated with consistent condom use. It is better to give more emphasis on health education and counseling service about consistent condom use for PLWHA who are on ART during follow-up especially for those who came from rural areas.